Magnetic resonance imaging to assess the effect of exercise training on pulmonary perfusion and blood flow in patients with pulmonary hypertension - Ley, Sebastian; Fink, Christian; Risse, Frank; Benjamin, Nicola; Fischer, Christine; Ley-Zaporozhan, Julia; Kauczor, Hans-Ulrich; Klose, Hans; Grünig, Ekkehard (European radiology, 2013)
To evaluate whether careful exercise training improves pulmonary perfusion and blood flow in patients with pulmonary hypertension (PH), as assessed by magnetic resonance imaging (MR).
Published online: 12 August 2012
Gesehen am 17.02.2022